DIGITALIZATION'S IMPACT ON THE SUSTAINABILITY OF PRINT MEDIA: A CASE STUDY OF RADAR SULBAR DAILY IN MAMUJU REGENCY - Ria Ainun Hijriani; Andi Indra Martini; Jamaludin Kamarudin (SEAN Institute, 2023)
This study investigates the impact of digitalization on the performance of the print media industry, with a specific focus on Radar Sulbar Daily in Mamuju Regency. Qualitative data were collected through observations and interviews with key personnel. The research utilized triangulation to ensure data validity. Data analysis involved reduction, presentation through descriptions and narratives, and drawing conclusions. The SWOT analysis method was applied to assess strengths, weaknesses, opportunities, and threats, aiding in strategy formulation. The study emphasizes the challenges and opportunities print media faces in the digital era, highlighting the need for adaptation to remain competitive. Overall, it offers insights into the evolving media landscape and the importance of embracing digital trends for long-term viability.